Pengaruh Motivasi Kerja, Komitmen Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan CV. Budi Mulya - M Zainul Abidin; Hadi Sunaryo; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of work motivation, organizational commitment and work discipline on the performance of employees of CV. Budi Mulya in the Manisrenggo Village, Kediri City. The sampling technique used was purposive sampling. The data sample was 36 respondents. Methods of data collection using a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that simultaneously work motivation, organizational commitment and work discipline had a positive effect on employee performance, partially work motivation, organizational commitment and work discipline had a positive and significant effect on employee performance. Keywords: Work Motivation, Organizational Commitment, Work Discipline, Employee Performance